S.D. Terr. Pen. Code (1877), § 457 as codified in S.D. Rev. Code, Penal Code (1903), §§ 470-471. - (:unkn) unknown (General Publisher, 1877)
Prohibited the carrying, “whether concealed or not,” of any slungshot, and prohibited the concealed carrying of any firearms or sharp or dangerous weapons.
--
Keywords: CARRY